(untitled) (Journal of the College of Basic Education, 2022)
Digital image applications were widespread at the beginning of the seventies and with the third generation of computers as they provided the speed and storage capabilities necessary for the practical implementation of image processing algorithms. After that, this field witnessed rapid growth and became the subject of research and study for several disciplines such as engineering, computer and information sciences, statistics, physics, chemistry, and life sciences. In the current research, the spatial domain method was used by image segmentation, which is one of the steps of image analysis.